FAKTOR-FAKTOR YANG MEMENGARUHI TINGKAT UNDERPRICING SAHAM PERDANA PADA PERUSAHAAN NON-KEUANGAN GO PUBLIC - Yustisia, Natali; Roza, Mailana (Media Riset Akuntansi, 2012)
This  research  aims  to  evaluate  the  effect  of  the  underwriter’s  reputation,  auditor’s reputation,  company’s  profitability  (ROE),  size  of  company  and  the  percentage  of  stocks offered  to  the  public,  towards  the  underpricing  level  that  happened  in  Indonesia  Stock Exchange  (IDX)  at  initial  public  offering  (IPO).    Samples  obtained  were  as  many  as  45 companies  listing  in  IDX  during  the  period  of  2006-2008.    The  data  are  analyzed  by using  multiple  linear  regression  with  level  of  significance  (á)  5%.    The  results  of  this research  indicated  that  only  the underwriter’s  reputation influence the  underpricing  level, individually. Keywords: underwriter’s  reputation,  auditor ’s  reputation,  Return  on  Equity,  size  of company,  the  percentage  of  stocks  offered  to  the  public,  underpricing